2020
DOI: 10.1242/dev.183814
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt/β-catenin activity and differential epigenetic marks direct sexually dimorphic regulation of Irx3 and Irx5 in developing mouse gonads

Abstract: Members of the Iroquois B (IrxB) homeodomain cluster genes, specifically Irx3 and Irx5, are crucial for heart, limb and bone development. Recently, we reported their importance for oocyte and follicle survival within the developing ovary. Irx3 and Irx5 expression begins after sex determination in the ovary but remains absent in the fetal testis. Mutually antagonistic molecular signals ensure ovary versus testis differentiation with canonical Wnt/β-catenin signals paramount for promoting the ovary pathway. Nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 80 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, Lefty1 and Lefty2 genes were found to be specifically expressed in the male gonad, which have been reported to regulate the male germ cell fate segmentation 37 . Several genes such as Irx3 38 and Lgals7 , were identified specifically expressed in female gonad. A set of gonad-specific genes in both female and male, such as Dppa3 and Text19.1 , was also identified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Lefty1 and Lefty2 genes were found to be specifically expressed in the male gonad, which have been reported to regulate the male germ cell fate segmentation 37 . Several genes such as Irx3 38 and Lgals7 , were identified specifically expressed in female gonad. A set of gonad-specific genes in both female and male, such as Dppa3 and Text19.1 , was also identified (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Sp5 encodes a Wnt/β-catenin effector ( Kennedy et al, 2016 ), suggesting that this signalling pathway might be important for ampullary organ development. Indeed, one of the other ampullary organ-restricted genes, Irx5 , is directly upregulated by Wnt/β-catenin signalling in somatic cells of the gonad ( Koth et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility would be the participation of the implicated AIC genes in a sexually dimorphic pathway such as Wnt signalling, which has been linked to female developmental disorders in X-linked, Wnt-related genes such as DDX3X , USP9X and PORCN [ 60 , 61 , 62 ]. In mice, the Wnt signalling pathway directs sexually dimorphic autosomal gene expression in specification of ovaries and testis [ 63 ] and in the adrenal cortex, activation of Wnt signalling by Rspo1 results in adrenal cortical hyperplasia in females but cortical thinning in males [ 64 ]. We identified a WNT8B variant that affected Wnt signalling as measured using the TOPflash assay; while Shrauwen et al showed upregulation of the Wnt receptor LRP5 using RNA-Seq, and also discovered a pathogenic variant in TEAD1 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%